Plasmatic Levels of HSP90α at Diagnosis: A Novel Prognostic Indicator of Clinical Outcome in Advanced Lung Cancer Patients Treated With PD-1/PD-L1 Inhibitors Plus Chemotherapy - Chen, Shubin; Yu, Qitao; Zhou, Shaozhang (Frontiers in Oncology, 2021)
Background: The purpose of this study was set to investigate the prognostic role of plasmatic levels of HSP90α at diagnosis in advanced lung cancer patients treated with PD-1/PD-L1 inhibitors plus chemotherapy. Methods: A total of 137 advanced lung cancer patients treated with PD-1/PD-L1 inhibitors plus chemotherapy admitted to the Guangxi Medical University Cancer Hospital were enrolled in this study. Smooth curve fitting was conducted to address the nonlinearity of HSP90α and PFS and OS. We calculated the inflection point using a recursive algorithm. Kaplan–Meier survival analysis and Cox’s proportional hazards regression model were used to assess the prognostic value of HSP90α for PFS and OS. Subgroup analysis was acted to evaluate the relationship between high HSP90α and disease progression and death risk. Results: The average age of patients was 58.6 ± 9.8 years old, and 73.7% of them were men. We divided patients according to their plasmatic levels of HSP90α into low (HSP90α<52.7 ng/ml) group and high (HSP90α≥52.7 ng/ml) group. Kaplan-Meier analysis showed a shorter PFS and OS for the high group with log-rank p< 0.05. Univariate and multivariate analyses indicated that high HSP90α was associated with an increased risk of disease progression and death after fully adjusted potential confounders with hazards ratio (HR) 1.8 (95%CI = 1.0‐3.2) and HR 2.4 (95%CI = 1.1-5.1), respectively (P-value < 0.05). After stratification by subgroup analysis, the relationship between high HSP90α and the risk of disease progression and death was consistent across all patient subgroups . Conclusion: Plasmatic levels of HSP90α at diagnosis can be considered as a potential independent prognostic marker of advanced lung cancer patients treated with PD-1/PD-L1 inhibitors plus chemotherapy, a further large-scale prospective validation study is needed to determine whether these results are widely applicable